Intercropping Compatibility of Cheena and Kaon with Groundnut at Charland Condition of Bangladesh - Karim, M R; Chowdhury, J A; Kakon, S S; Ali, M Z; Khan, M A H; Mian, M A K; Rahman, J (Bangladesh Agronomy Journal, 2025)
Intercropping is a sustainable cropping strategy that enhances productivity, resource-use efficiency, and economic returns, particularly in fragile agro-ecological zones such as charlands in Bangladesh. This study evaluated the intercropping compatibility of groundnut (Arachis hypogaea L.) with two minor cereals—cheena (Panicum miliaceum L.) and kaon (Setaria italica L.)—under varying row arrangements in charland ecosystems during the 2024–25 cropping season. The treatments included four intercropping systems: groundnut:cheena (4:1 and 4:2), groundnut:kaon (4:1 and 4:2), and three sole cropping systems: groundnut, cheena, and kaon. Agronomic yield attributes, groundnut equivalent yield (GEY), economic returns, land equivalent ratio (LER), competitive ratio (CR), and relative crowding coefficient (RCC) were analyzed. Sole groundnut produced the highest pod yield (2.18 t ha−1), while intercropping reduced individual groundnut yield. However, overall system productivity improved under intercropping, with groundnut:cheena (4:2) producing the highest GEY (3.20 t ha−1), gross return (Tk 256,200 ha−1), gross margin (Tk 201,100 ha−1), and benefit–cost ratio (4.65). Groundnut:kaon (4:2) also performed strongly with a GEY of 3.14 t ha−1 and a benefit–cost ratio of 4.62. All intercropping treatments recorded LER > 1.0, indicating yield advantage over sole cropping. Competitive indices revealed that kaon was more aggressive than cheena, but cheena-based systems were more complementary and profitable. The findings suggest that intercropping groundnut with cheena (particularly at a 4:2 row proportion) is the most compatible and profitable option for charland conditions, ensuring enhanced productivity, profitability, and sustainability. Bangladesh Agron. J. 2025, 28(1): 17-22